Comparative study of 940 nm and 1450 nm near infrared sensor for glucose concentration monitoring - Kiki Prawiroredjo; Engelin Shintadewi Julian (Universitas Ahmad Dahlan, 2019)
In order to manage their blood glucose level, diabetics have to test their blood glucose level regularly. Unfortunately, the current blood glucose measurement device is uncomfortable, painful, event costly for the diabetics; therefore, a lot of effort is given to develop a noninvasive blood glucose meter. We studied the potential of two near infrared wavelength i.e. 1450 and 940 nm as glucose sensor. Each sensor consists of a light emitting diode (LED) as light source, a photodiode that is sensitive to that wavelength, transimpedance amplifier, and filters. An acrylic box size 5cmx1cmx5cm was used as glucose solution container. The LED and photodiode were located at each side of box width, at 1 cm distance. The container was than filled with various concentrations of glucose solution, and the sensor output voltages were measured. The results show that for glucose concentration 0 to 500 mg/dl, the output voltages of the 1450 nm sensor tend to lower when the glucose concentration is higher, therefore it has the potential to be used as glucose sensor. Different result is obtained from the 940 nm sensor where the output voltages were remained the same when the glucose concentration was varied.